Religião e lutas identitárias por cidadania e justiça: Brasil e Argentina - Joanildo A. Burity (Universidade do Vale do Rio dos Sinos (UNISINOS), 2009)
One of the recent developments in the Latin American context is surely the growing public impact of identity claims and disputes, which are connected to demands for citizenship rights and justice or for political representation. The cultural dimension of this process is, inextricably, linked with the political one, both in a symbolic and a political sense. This article explores one of the particular instances of the process: the public emergence of religions and its relation to endogenous changes to Latin American societies and to the effects of global flows on the dynamics of the former. The analysis, which is part of a broader comparative study under way will focus on the fi eld of Christianity in Brazil and Argentina.